Stabilization of short telomeres and telomerase activity accompany immortalization of Epstein-Barr virus-transformed human B lymphocytes. - Counter, C M (1994)
We have measured telomere length and telomerase activity throughout the life span of clones of human B lymphocytes transformed by Epstein-Barr virus. Shortening of telomeres occurred at similar rates in all populations and persisted until chromosomes had little telomeric DNA remaining. At this stage, some of the clones entered a proliferative crisis and died. Only clones in which telomeres were stabilized, apparently by activation of telomerase, continued to proliferate indefinitely, i.e., became immortal. Since loss of telomeres impairs chromosome function, and may thus affect cell survival, we propose that telomerase activity is required for immortality. We have now detected this enzyme in a variety of immortal human cells transformed by different viruses, indicating that telomerase activation may be a common step in immortalization.